UK advertising and the law: where regulation meets new challenges - Haftke, Mark (Henry Stewart Talks, 2009)
Problems posed by online technologies to existing regulatory regime for advertising in the UK, Review of current regulations, Consideration of advertising related technology developments, Privacy issues, behavioral profiling, key word auctions, price comparisons, New legislation on consumer protection, misleading marketing and electronic communications
Archived at 2022/04/11